Drill string's axial force transfer law in slide directional drilling in underground coal mine. (December 2022) - Xu, Bao-Long; Liu, Song-Yong; Li, Hong-Sheng
Highlights: A novel numerical dynamic model of drill string in full-scale is built. Drill string's axial force transfer law under multi-factors is obtained. The theoretical analysis result conforms well to the field drilling test. Abstract: During the slide directional drilling with long directional near-horizontal drilling technology, the weight on bit (WOB) at the bottom of the hole is exerted by pushing the drill pipe with the power head of the orifice drill. With the increase of drilling depth, the friction resistance between drill string and hole wall also goes up, resulting in problems including insufficient WOB, low drilling efficiency, and surge of feeding pressure. If the orifice feeding pressure continues to rise, the drill string will buckle or fracture. In our study, the field test method is adopted to explore the drilling string's axial pressure transfer law. By comparatively analyzing different stratigraphic characteristics of five directional boreholes with an average radius of deflection, the deep-hole drill string transmitting pressure model with nine curvature radiuses is set up for simulating the relationships between drill string friction, hole depth, and strata characteristics under different working conditions. The results show that when the hole is relatively shallow, the relationship between the friction resistance and the hole depth is basically linear, which gradually develops into an exponential one with the increase in the hole depth. For the borehole with a curvature radius less than 200 m, the friction resistance is greatly affected. The softer the formation is, the greater the linear range of friction resistance becomes with the increase in the hole depth, the latter the hole depth with an exponential growth occurs, and the longer the limit depth is. The findings reveal the axial pressure transfer law of the drill string, which will facilitate future design of the drilling hole, optimize the control of drilling trajectory, and matter a lot to engineering practices.